2018
DOI: 10.1093/annonc/mdy105
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy followed by chemoradiation and surgery with and without cetuximab in patients with resectable esophageal cancer: a randomized, open-label, phase III trial (SAKK 75/08)

Abstract: NCT01107639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 12 publications
(15 reference statements)
1
82
3
1
Order By: Relevance
“…The data from our study showed such an intermediate prognostic group for patients with 1–50% VTCs in the Cologne Regression scale and for the Mandard classification combining TRG1 and TRG2, but not for the ypT category. For Mandard classification, such a medium prognostic group for oesophageal cancer patients was not found in two studies . Using the percentage of VTCs compared to the original volume of the tumour, Swisher et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from our study showed such an intermediate prognostic group for patients with 1–50% VTCs in the Cologne Regression scale and for the Mandard classification combining TRG1 and TRG2, but not for the ypT category. For Mandard classification, such a medium prognostic group for oesophageal cancer patients was not found in two studies . Using the percentage of VTCs compared to the original volume of the tumour, Swisher et al .…”
Section: Discussionmentioning
confidence: 99%
“…For Mandard classification, such a medium prognostic group for oesophageal cancer patients was not found in two studies. 33,34 Using the percentage of VTCs compared to the original volume of the tumour, Swisher et al described such a medium prognostic group for patients with oesophageal cancer after neoadjuvant therapy with 1-50% VTCs. 35 Similar results are described by Langer et al 36 According to our results, the group of patients with <10% VTC has a very good prognosis, comparable with those patients with pCR of the primary tumour, and a better prognosis compared to those with 10-50% VTC.…”
Section: Discussionmentioning
confidence: 99%
“…The two trials that studied SCRT did not show benefit in any of the variables evaluated. This strategy was also re-evaluated with modifications, i.e., induction chemotherapy (docetaxel, infusional FU, cisplatin) followed by neoadjuvant chemoradiation followed by surgery, with or without cetuximab [48]. The addition of cetuximab did improve the locoregional control but did not translate in survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This additional analysis was planned after initiation of the study but before primary analysis. The study design and clinical efficacy endpoints have been published in detail [8].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with locally advanced and resectable oesophageal cancer are treated with multimodal therapy in curative intention with 5-year overall survival rates of at least 50% and platinum-based chemotherapy is an established part of the treatment [8][9][10]. Due to the paucity of prospective data on VTEs in resectable oesophageal cancer the aim of this analysis was to describe the rate and pattern as well as potential risk factors of VTEs (such as histologic subtype and the "Khorana risk factors" listed above) in patients with resectable oesophageal cancer with multidisciplinary treatment within an international phase lll trial.…”
Section: Introductionmentioning
confidence: 99%